Advances in Polymeric Materials for Biomedical Applications - Radecka, Iza; Kowalczuk, Marek M. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Significant research efforts are currently being undertaken in the field of natural and synthetic polymers for a range of biomedical applications. (Co)polymer molecular structure, topology, self-assemblies, biodegradation, and hydrophobicity are of biomaterial importance for intrinsically biocompatible polymer systems. This book is comprised of nine chapters, published previously as original research contributions of the Special Issue focused on advances in polymeric materials for biomedical applications. The authors of these contributions are predominantly from central European countries, Italy and the United Kingdom. The content of this book will be of interest to scientists, scholars and students working in this area of knowledge, reflecting the progress in the development of advanced natural and synthetic polymer biomaterials.